(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2015)
This article is a reflection on the processes of experimentation in the contemporary sculpture, organized in three visions, the first one from the significant character of the material as fundamental element in the sculpture, the second one from the history as foundation for the sculptural contemporary construction and the third one, from the scientific investigation as methodological construction (mixed, experimental and interpretive approach) of the experimentation realized in the Experimental Workshop of Sculpture of the Bachelor of Arts, University Centroccidental Lisandro Alvarado. We achieved an investigation that combines the artistic with the academic fact done through analysis, experimentation and reflection continues concerning the contemporary sculpture.